Improving Arabic text categorization using Neural Network with SVD - Harrag, F.; Al-Qawasmah, E. (Journal of Digital Information Management, 2010)
In this paper, we present a model based on the Neural Network (NN) for classifying Arabic texts. We propose the use of Singular Value Decomposition (SVD) as a preprocessor of NN to reduce the data in terms of both size as well as dimensionality so that the input data become more classifiable and faster for the convergence of the training process used in the NN model. To test the effectiveness of the proposed model, experiments were conducted using an in-house collected Arabic corpus for text categorization. The results showed that the proposed model was able to achieve high categorization effectiveness as measured by precision, recall and F-measure. Experimental result shows that the ANN model using SVD is better than the basic ANN on Arabic text classification.
Keywords: Arabic language; MLP; Neural network; Singular Value Decomposition; Text categorization

Dual watermarking scheme for copyright protection and authentication - Bhatnagar, G.; Raman, B.; Swaminathan, K. (Journal of Digital Information Management, 2009)
Digital Watermarking is used for copyright protection and authentication of digital media-image/audio/video data. In this paper, a novel dual watermarking scheme is described based on Discrete Wavelet Transforms (DWT) and Singular Value Decompositions (SVD). Unlike the existing dual watermarking schemes, both the watermark embedded using DWT and SVD are invisible in the proposed scheme. For embedding, both the images are transformed into Wavelet domain and SVD is performed further on both the images. Subsequently the singular values are summed up to find the new set of singular values. Both the watermarks get embedded in the same manner. A reliable watermark extraction scheme has been developed for the extraction of the watermarks from the distorted image. Experimental evaluation demonstrates that the proposed scheme is capable of withstanding variety of attacks.
Keywords: Digital dual watermarking; Gray-scale logo; Multiresolution analysis; Singular Value Decomposition; Wavelet Transform; Zig-zag sequence